Predict the financial markets crises (forecasting models and their applicability in the Arab Financial Markets) - Saiah, Abdalla Ab Sinusi; Mostafa, Mousa Rahil; Bon, Abdul Talib; Ng, Kim Soon (AENSI Publishing Corporation, 2011)
This paper aims to the possibility of a model or reliable way to predict financial crises or reduce them. In addition, when financial crises occur in the financial market given they quickly move to other financial market, and cause negative effects on other financial market, the meaning of that financial markets around the world are interdependent with each other directly or indirectly. Therefore, the financial markets demand to determines the form or the way to avoid financial crises or reduce the professions. The results of this study was that the financial crisis occurs when (the rate of domestic credit growth high, the evaluation of the exchange rate high compared to the general trend, the foreign interest rate is high, the foreign investment less than the external debt. ,the ratio of money multiplier high compared with the reserves and when there is a large deficit in the current account). If any financial market can control these factors, this does not mean that this market is to be subjected to a financial crisis that the financial crisis may occur in other financial market and raised up to this market. So, the way in which they can achieve the kind of financial crises is to establishment of the global financial markets to develop criteria for evaluating the performance of financial markets and should be the six criteria we mentioned are the most important criteria and indicators used in the evaluation. The financial market may be subjected to a financial crisis if there is any negative deviation from the criteria and assessment indicators for more than six months. In fact, these indicators measure the performance of the economic environment in which it operates the financial market, which affected directly the performance of the financial market in any country, and therefore these indicators and standards are an important tools for economic departments in improving the economic performance and development at the state level.